A candidate regulatory variant at the TREM gene cluster associates with decreased Alzheimer's disease risk and increased TREML1 and TREM2 brain gene expression. Issue 6 (8th December 2016) - Carrasquillo, Minerva M.; Allen, Mariet; Burgess, Jeremy D.; Wang, Xue; Strickland, Samantha L.; Aryal, Shivani; Siuda, Joanna; Kachadoorian, Michaela L.; Medway, Christopher; Younkin, Curtis S.; Nair, Asha; Wang, Chen; et al.
Abstract: Introduction: We hypothesized that common Alzheimer's disease (AD)‐associated variants within the triggering receptor expressed on myeloid ( TREM ) gene cluster influence disease through gene expression. Methods: Expression microarrays on temporal cortex and cerebellum from ∼400 neuropathologically diagnosed subjects and two independent RNAseq replication cohorts were used for expression quantitative trait locus analysis. Results: A variant within a DNase hypersensitive site 5′ of TREM2, rs9357347‐C, associates with reduced AD risk and increased TREML1 and TREM2 levels (uncorrected P  = 6.3 × 10 −3 and 4.6 × 10 −2, respectively). Meta‐analysis on expression quantitative trait locus results from three independent data sets ( n  = 1006) confirmed these associations (uncorrected P  = 3.4 × 10 −2 and 3.5 × 10 −3, Bonferroni‐corrected P  = 6.7 × 10 −2 and 7.1 × 10 −3, respectively). Discussion: Our findings point to rs9357347 as a functional regulatory variant that contributes to a protective effect observed at the TREM locus in the International Genomics of Alzheimer's Project genome‐wide association study meta‐analysis and suggest concomitant increase in TREML1 and TREM2 brain levels as a potential mechanism for protection from AD. Highlights: rs9357347‐C, 5′ TREM2, is associated with reduced AD risk ( P uncorrected  = 1 × 10 −03 ). TREM2 and TREML1 are the only TREM cluster genes with reliable brain expression. Higher brain levels of TREM2 and TREML1 associate with rs9357347‐C. rs9357347 is predicted to affect transcription factor binding (SP1 and PPAR). Increased gene expression of TREML1 and TREM2 may reduce AD risk.